1999
DOI: 10.1037/0021-843x.108.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Differential cognitive response to a mood challenge following successful cognitive therapy or pharmacotherapy for unipolar depression.

Abstract: This study examined the nature of cognitive reactivity to mood changes in formerly depressed patients. Patients who recovered either through cognitive-behavior therapy (CBT; N = 25) or through pharmacotherapy (PT; N = 29) completed self-reported ratings of dysfunctional attitudes before and after a negative mood induction procedure. In response to similar levels of induced sad mood, PT patients showed a significant increase in dysfunctional cognitions compared with patients in the CBT group. To evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
268
0
11

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 300 publications
(295 citation statements)
references
References 37 publications
16
268
0
11
Order By: Relevance
“…Several studies have found support for the prediction of relapse by cognitive reactivity after remission from MDD (233 patients; Kuyken et al, 2010;Segal, Gemar, & Williams, 1999;Segal et al, 2006). Though, one recent study found no evidence for cognitive reactivity in patients remitted from MDD (Jarrett et al, 2012), whereas Lethbridge and Allen (2008) were unable to corroborate the predictive validity of cognitive reactivity (52 patients).…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Several studies have found support for the prediction of relapse by cognitive reactivity after remission from MDD (233 patients; Kuyken et al, 2010;Segal, Gemar, & Williams, 1999;Segal et al, 2006). Though, one recent study found no evidence for cognitive reactivity in patients remitted from MDD (Jarrett et al, 2012), whereas Lethbridge and Allen (2008) were unable to corroborate the predictive validity of cognitive reactivity (52 patients).…”
mentioning
confidence: 90%
“…Until now, only post-treatment cognitive reactivity had been examined (Kuyken et al, 2010;Segal et al, 1999Segal et al, , 2006. We therefore repeated previous analyses for post-treatment cognitive reactivity and cognitive extremity reactivity.…”
Section: Prediction Of 55-year Relapse By Cognitive Reactivity and Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This piece was remastered at half speed and runs for approximately 8 min. This piece, played at half speed, has been shown to be very effective in inducing a negative or depressed mood (e.g., Fresco, Heimberg, Abramowitz, & Bertram, 2006;Segal et al, 1999Segal et al, , 2006. A meta-analysis of musical mood induction procedures found a good effect size (Cohen's f ϭ .56) for sad mood inductions including, but not limited to, this Prokofiev piece played at half speed (Westermann, Spies, Stahl, & Hesse, 1996).…”
Section: Emotion Evocation Challengementioning
confidence: 99%